Epifania e enigma: as Índias de Cecília Meireles e Antonio Tabucchi - Rodrigues, Edison de Abreu (2013)
The objective of this research is to analyze comparatively the book: Poemas Escritos na Índia, by Cecilia Meireles and Noturno Indiano, by Antonio Tabucchi, analyzing the bias of the journey and alterity, comprehending how is the search for the otherness sense through the journey report . To achieve our goal, we propose the following hypothesis: it is possible that, in both works, the sense of alterity be constructed from the relationship between India, the poet lyric persona and the investigative narrator's character; Cecilia Meireles externs her poetic metaphysical experiences building a sense of otherness through contemplation of places and people, while Antonio Tabucchi builds otherness through investigation of a fleeting, nomadic shadow and a sense of missing thing. This research is based upon the relation between the concepts of the journey and alterity, the reflections of Octavio Paz, Wladimir Krysinski, Tzvetan Todorov and Mikhail Bakhtin. About the narrator traveler, the thoughts of Walter Benjamin and Michel Onfray proved to be of great value; the character of the night in the literature has as a parameter the conceptualization of Maurice Blanchot. Among the research results, we emphasize that despite building a sense of alterity in different ways, it is the journey that provides support for the search of this other being that is within us and, that the literary creation of an India capable to encompass the multiplicity of humanity, awakens in man the divine character and takes him to recognize himself